ANALISIS PERAN LEMBAGA AMIL ZAKAT INFAQ DAN SHODAQOH “LAZISNU” CABANG NGANJUK DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Fahdina Naila Rohmah; Aan Nasrullah (Commodities, Journal of Economic and Business, 2024)
Poverty is a great danger for humanity and not a few human beings who fall into civilization only because of poverty. As a solution to alleviating poverty that is vulnerable to this country, the government with various programs implemented is trying to be able to reduce the poverty chain. One potential funding source is zakat, infaq and shodaqoh funds, both managed by the Amil Zakat Institute (LAZ). The purpose of this study is to explain the role of the Amil Zakat Infaq Shodaqoh "LAZISNU" Nganjuk Branch in improving community welfare; as well as to explain the mechanism of Zakat, Infaq and Shodaqoh Pentasyarufan at the Amil Zakat Infaq Shodaqoh "LAZISNU" Nganjuk Branch Institution. This research is a type of field research that is qualitative descriptive. The presentation model of this research is carried out by describing the object being studied as is with qualitative statements. The steps in data collection are using observation, interview and documentation data to the parties involved in the episcopalism. The results showed that the legal basis used by LAZISNU was in accordance with the Zakat Law No. 23 of 2011 but in reality the community could not be said to be prosperous.